RANCANG BANGUN MODUL PRAKTIKUM KUALITAS DAYA LISTRIK PADA SIMULATOR RUMAH TINGGAL 450 VA - Budi, Heri Budi Utomo; Hutajulu, Olnes; Pangaribuan, Wanapri (Universitas Negeri Medan, 2024)
Technological developments, including electronic-based electrical equipment, have experienced rapid development in the last ten years. This equipment is found in buildings and industrial buildings as far as residential homes, generally alternating current (AC/Alternating Current) loads, including linear and nonlinear loads. The use of nonlinear loads causes a decrease in the quality of electrical power and shortens the life of electrical equipment. The new implementation of curriculum, Kampus Merdeka, in the electrical engineering study program majoring in electrical engineering, Bandung State Polytechnic, a new course in the curriculum, namely Electrical Power Quality, must be implemented. Creating a practical module simulator for electrical power quality in residential homes is necessary to support the teaching and learning process. This study aims to design and test the quality practice model of residential electrical power. The research method is using experimental methods. The result of this study for nonlinear loads, mixed load one and mixed load 2, have THDi and TDD values exceeding IEEE standard No. 19 of 2014 and have a True PF value smaller than Distortion PF. It shows that the electrical power quality of the residential simulator's electrical system is poor, so a passive filter or active filter is needed to improve the quality of electrical power in the residential simulator.